Derivation of a Screening Tool to Identify Patients with Right Ventricular Dysfunction or Tricuspid Regurgitation after Negative Computerized Tomographic Pulmonary Angiography of the Chest. (1st March 2015) - Kline, Jeffrey A.; Russell, Frances M.; Lahm, Tim; Mastouri, Ronald A.
Abstract : Many dyspneic patients who undergo computerized tomographic pulmonary angiography (CTPA) for presumed acute pulmonary embolism (PE) have no identified cause for their dyspnea yet have persistent symptoms, leading to more CTPA scanning. Right ventricular (RV) dysfunction or overload can signal treatable causes of dyspnea. We report the rate of isolated RV dysfunction or overload after negative CTPA and derive a clinical decision rule (CDR). We performed secondary analysis of a multicenter study of diagnostic accuracy for PE. Inclusion required persistent dyspnea and no PE. Echocardiography was ordered at clinician discretion. A characterization of isolated RV dysfunction or overload required normal left ventricular function and RV hypokinesis, or estimated RV systolic pressure of at least 40 mmHg. The CDR was derived from bivariate analysis of 97 candidate variables, followed by multivariate logistic regression. Of 647 patients, 431 had no PE and persistent dyspnea, and 184 (43%) of these 431 had echocardiography ordered. Of these, 64 patients (35% [95% confidence interval (CI): 28%–42%]) had isolated RV dysfunction or overload, and these patients were significantly more likely to have a repeat CTPA within 90 days ( P =. 02, χ 2 test). From univariate analysis, 4 variables predicted isolated RV dysfunction: complete right bundle branch block, normal CTPA scan, active malignancy, and CTPA with infiltrate, the last negatively. Logistic regression found only normal CTPA scanning significant. The final rule (persistent dyspnea + normal CTPA scan) had a positive predictive value of 53% (95% CI: 37%–69%). We conclude that a simple CDR consisting of persistent dyspnea plus a normal CTPA scan predicts a high probability of isolated RV dysfunction or overload on echocardiography.